2022
DOI: 10.3390/coatings12091329
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mortar with Fe2O3 Nanoparticles for Radiation Shielding Application

Abstract: The current study aims to investigate the radiation shielding properties of mortar samples with Fe2O3 nanoparticles for radiation protection applications. For the reference mortar (free Fe2O3 nanoparticles) and the mortar with different concentrations of Fe2O3 nanoparticles, we experimentally measured the transmission factor (I/I0) for four different thicknesses of the prepared mortar. The I/I0 results indicated that the transmission of the photons through the mortars decreases with increases in the mortar’s t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…From the count rate and sample thickness calculations, the µ (cm −1 ) can be estimated by the next law 10 , 19 , 20 : …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the count rate and sample thickness calculations, the µ (cm −1 ) can be estimated by the next law 10 , 19 , 20 : …”
Section: Methodsmentioning
confidence: 99%
“…al. examined mortar samples with varied Fe 2 O 3 nanoparticle concentrations for radiation protection 10 . With increasing mortar thickness, photon transmission diminishes, according to I/I0 findings.…”
Section: Introductionmentioning
confidence: 99%
“…Various dense materials such as tungsten, bismuth, copper, and steel are considered good shielding materials. However, different composites based on polymers, glasses, alloys, and mortars containing fillers, such as micro- and nanoparticles, have been extensively studied as alternative radiation-shielding materials which are suitable for the desired applications [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, tungsten carbide, which has a high atomic number and excellent shielding ability, has been proposed as a replacement for lead, which was previously the industry standard for radiation shielding [22]. Studies have shown that tungsten carbide can improve the radiation shielding properties of cement pastes, while also offering greater resistance and hardness [23]. Pioneering studies in this field include the work of Smith et al [14], who investigated the use of bismuth oxide nanoparticles for radiation shielding, and the study by Lee et al [15], who explored the use of Fe 3 O 4 nanoparticles for improving the radiation shielding properties of cement pastes.…”
Section: Introductionmentioning
confidence: 99%